Vascular flora of Serra do Japi Biological Reserve, Jundiaí, southeastern Brazil - Lombardi, Julio Antonio [UNESP]; Carvalho, Carolina da Silva [UNESP]; Biral, Leonardo [UNESP]; Saka, Mariana Naomi [UNESP]; Hieda, Sean Miki [UNESP] (Instituto de Pesquisas Jardim Botânico do Rio de Janeiro, 2012)
Amostragem florística foi feita em áreas da Reserva Biológica Municipal da Serra do Japi, Jundiaí, Estado de São Paulo, incluíndo fisionomias de floresta semidecídua montana, classificada como parte das formações da Mata Atlântica. Foram encontradas 661 espécies em 129 famílias, as dez fanerogâmicas mais diversas foram: Asteraceae (56 espécies), Fabaceae (37), Rubiaceae (29), Poaceae (25), Solanaceae (24), Cyperaceae (19), Euphorbiaceae (19), Orchidaceae (19), Melastomataceae (17), e Piperaceae (17). O acréscimo de 322 espécies adicionais compiladas de listagens florísticas suplementares eleva, para a Serra do Japi em geral, o número registrado a 976 espécies em 141 famílias. Comparada a outros levantamentos florísticos na Mata Atlântica, esses resultados demonstram a diversidade florística da área estudada e ressaltam o valor da preservação da vegetação nessa região altamente urbanizada.

Floristic sampling was carried out in Serra do Japi Biological Reserve, Jundiaí, state of São Paulo, Brazil, including physiognomies of semideciduous montane forest, a type of forest formation within the Atlantic Forest domain. Six hundred and sixty one species distributed in 129 families were recorded; the ten most diverse phanerogam families were: Asteraceae (56 species), Fabaceae (37), Rubiaceae (29), Poaceae (25), Solanaceae (24), Cyperaceae (19), Euphorbiaceae (19), Orchidaceae (19), Melastomataceae (17), and Piperaceae (17). The addition of 322 species from other floristic surveys increased the number of species of Serra do Japi to 976, distributed in 141 families. Compared to other floristic surveys carried out in the Atlantic Forest, our results highlight the floristic diversity of the study area and the importance of preserving the vegetation of this highly urbanized region.
Flora vascular da Reserva Biológica Municipal da Serra do Japi, Jundiaí, SP
Keywords: Brasil; floresta semidecídua montana; florística; Mata Atlântica; plantas vasculares; Brazil; semideciduous montane forest; floristic; Atlantic Forest; vascular plants